A Study on Management of Administrative Challenges and Market Strategies in the Implementation of Carbon Tax in Indonesia - Ardhimansyah, Trio; Khaddafi, Muammar (Sahabat Publikasi, 2024)
This research discusses administrative challenges and market strategies in implementing a carbon tax in Indonesia. The carbon tax was introduced through the 2021 Harmonization of Tax Regulations Law to control CO2 emissions from fossil fuels such as coal, oil and natural gas. Key challenges include administrative complexity, strong inter-agency coordination, effective monitoring systems, and consistent law enforcement. The global carbon market in 2023 shows great potential for economically efficient emissions reductions, but implementing this model requires adapting to Indonesia's socio-economic landscape. The research method used is a qualitative approach with case studies, combining data from policy documents, interviews with tax experts, and local carbon market analysis. The research results show that the implementation of a carbon tax is faced with several major challenges, including a lack of accurate data on emissions, an immature monitoring system, and resistance from certain industrial sectors. Effective market management strategies, such as the allocation of tax revenues to sustainable projects, are key to mitigating negative economic impacts and encouraging investment in green technologies. This research makes a significant contribution to the understanding of the complexity of carbon tax implementation in developing countries and its relevance in the global context for achieving climate change goals.